POTRET KEMAMPUAN KOMUNIKASI DAN KEMELEKWACANAAN TEKNOLOGI GURU SD DI INDONESIA: DALAM PANDANGAN KEPALA SEKOLAH - Andayani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
Self-evaluation aims to determine the results of education in the form of transition fromthe world of higher education to the world of business and industry, educational output in the form ofself-assessment of the mastery and acquisition of competencies, the educational process in the formof evaluation of the learning process and the contribution of higher education to competencyacquisition and educational input in the form of further exploration of graduate information. Inaddition, through this self-evaluation education providers can find out how the program is organizedand the quality of service through the assessment of alumni and / or alumni users. Through this,education providers are able to improve and improve the quality of their services. The methodcontains the type of method or type of approach used, descriptions of qualitative and / or quantitativedata, data collection procedures, and analysis technique procedures. The type of research used in theimplementation of this research activity is a mixed descriptive quantitative and qualitative approach.Alumni users (Principals) assess that the competence of Primary School Teacher Education graduatesis very good. This shows that the alumni of the Elementary School Teacher Education study programcan apply the competencies obtained during college. There are aspects that are considered stilllacking and need to be improved, namely self-development.